Revitalizing Learning Concentration: Exploring Ice-Breaking Techniques to Improve Reading Proficiency in Elementary School - Nurul Aswar; Iramaya Iramaya (South Sulawesi Education Development (SSED), 2023)
This research aims to increase students' learning concentration in learning to read in class III elementary schools by applying the ice-breaking technique. This classroom action research was carried out over two cycles. Data was collected through observation, questionnaires, interviews and documentation. The research results show that the use of ice-breaking techniques is effective in increasing students' learning concentration. The questionnaire showed an increase in concentration from